Warszawianka – „paryżanka Północy”. O kobietach mody i modzie kobiecej Warszawy w dwudziestoleciu międzywojennym - Sola-Sałamacha, Nadia (Komunizm: System - Ludzie - Dokumentacja, 2023)
“Paris of the North” is a term that is frequently used with reference to pre-war Warsaw. It is still unclear who used it for the first time and what exactly they meant. Researchers and journalists eagerly quote this expression, either trying to justify or deny it. Aside from these academic discussions, it must be admitted that the capital city of the Second Polish Republic played the role of a Polish fashion centre for its citizens. The most renown fashion houses, ateliers and the most refined studios had their seats in Warsaw. Moreover, social life related to la mode was thriving here – the most splendid balls, major fashion shows and parades. Pre-war Warsaw attracted all stylishly-dressed people who, for various reasons, decided to complete their outfits in the country. Varsovian women also deserve to be called “Parisians of the North”. They were considered the most stylish and willing to follow the whims of fashion in Poland. This 64I. Studia article is a contribution to the role of Warsaw and the Varsovians in the fashion market of the Second Polish Republic. It discusses the main factors that determined the leading role of Warsaw in this domain: concentration of fashion and lifestyle magazines in Warsaw, an abundance of boutiques and tailor’s shops sewing and selling the most exquisite clothing, gallantry, footwear and accessories, as well as local theatre, cinema and artistic circles that were genuine role models following the latest trends.